2018
DOI: 10.1051/0004-6361/201832729
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of the outer halo of M 87 as mapped by planetary nebulae

Abstract: Aims. We present a kinematic study of a sample of 298 planetary nebulas (PNs) in the outer halo of the central Virgo galaxy M87 (NGC 4486). The line-of-sight velocities of these PNs are used to identify sub-components, to measure the angular momentum content of the main M87 halo, and to constrain the orbital distribution of the stars at these large radii. Methods. We use Gaussian mixture modelling to statistically separate distinct velocity components and identify the M87 smooth halo component, its unrelaxed s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 97 publications
(232 reference statements)
5
65
0
Order By: Relevance
“…On the other hand, the substructure explanation seems more aligned with GCs on possible tangential orbits in M87, since the Virgo cluster is known to be not fully relaxed. Moreover, substructure in the kinematics of planetary nebulae in the Virgo cluster have already been identified (Longobardi et al 2018). Although differentiating between these two mechanisms may probe difficult, our results indicate that localized tangentially biased orbits are not inconsistent with the accretion build up of the ICGC component.…”
Section: Intracluster Gcs As Kinematic Tracers Of the Dark Mattersupporting
confidence: 49%
“…On the other hand, the substructure explanation seems more aligned with GCs on possible tangential orbits in M87, since the Virgo cluster is known to be not fully relaxed. Moreover, substructure in the kinematics of planetary nebulae in the Virgo cluster have already been identified (Longobardi et al 2018). Although differentiating between these two mechanisms may probe difficult, our results indicate that localized tangentially biased orbits are not inconsistent with the accretion build up of the ICGC component.…”
Section: Intracluster Gcs As Kinematic Tracers Of the Dark Mattersupporting
confidence: 49%
“…M87 is (in projection) near the X-ray gas emission peak (e.g., Kellogg et al 1971) which is a good tracer for the potential minimum of the cluster. Moreover, the rising velocity dispersion profile of the surrounding planetary nebulae is steeper for M87 (Longobardi et al 2018) than for M49 (Hartke et al 2018), showing that intracluster planetary nebulae are more centered on M87 than on M49. The velocity dispersion profile of the globular clusters rises towards the outskirts of M87 (Côté et al 2001) but it falls towards the outskirts of M49 (Sharples et al 1998), showing that also the intracluster globular clusters are more centered on M87.…”
Section: Introductionmentioning
confidence: 94%
“…The kinematics of planetary nebulae in galaxies in the Virgo cluster have been studied by many authors (Longobardi et al 2013(Longobardi et al , 2015Hartke et al 2018;Longobardi et al 2018). These studies have found that in M87 and M49 the planetary nebulae of the ICL have different velocity and spatial distributions than those in the BCG halo.…”
Section: The Icl Is a Distinct Kinematic Component Separate From Thementioning
confidence: 99%